Evaluation of Diabetic Patients’ Knowledge to Cutoff Osteoporosis at Diabetes Center in Duhok City - Emad Elias Khaleel, Hussein Hadi Atiyah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patients with T1DM had two to six fold greater of fractures hazard compared to healthy individuals, with the dangerous being highest in T1DM females. In a recent study examining the factors that influence bone break hazards in T1DM adult persons, about 50% of the participants said they had at least one fracture after being diagnosed with diabetes. With comparison of non-diabetic persons, those with T2DM get a 1.2- to 3-fold high prevalence of breakage, especially hip fractures and moreover forearm and leg fracture. Break incidence appear higher in people with a BMI of less than 30 kg/m2 comparing to obese people, and does not appear to differentiate much by gender. Longer duration of diabetes, poor levels of physical activity, sugar and systemically corticosteroid usage, and advancing ages are all linked to an increased fracture risk in T2DM patients. Falls are another cause of fractures, particularly in diabetic women. Aims: The present study conducted to evaluate the patients’ knowledge to put off osteoporosis among a sample from a diabetes center in Duhok city. Methodology: A descriptive design aimed to evaluate diabetic patients’ knowledge from 25 November 2020 to 26 June 2021. In order to get reliable data and a representative sample, a nonprobability (accidental) sample of 27 patients were selected from the diabetes center of Azadi teaching hospital in Duhok city. The statistical data analysis approaches used in order to analyze and assess the results of the study under the application of the statistical package (SPSS) ver. (22.0). Descriptive statistical data analysis and inferential data analysis were used to analyze the finding of the present study Results: The finding of the present study shows female were more than male, constituted 19 (70.4%). The distribution of the gender variable is coincident in the study, as it is high of females, age was between (50- 60) and constituted 12 (44.4%). With regard to the marital status, most of the participants were married and constituted 23(85.2%). Regarding the educational level, most of the participants do not read and write (illiterate) and constituted 12 (44.4%). Most of the participants had low knowledge score of Relative sufficiency coefficient (RS%) less than (33.34) about osteoporosis. Conclusion: Most of the participants were suffer from type two diabetes mellitus and most of them who visit a diabetes center had minimum knowledge toward osteoporosis. Instructional programs with a large sample should be designed for all diabetic patients with both types of diabetes to improve their knowledge about osteoporosis